DESIGNING AND IMPLEMENTING CAR RENTAL SYSTEM - Rosha Assyifa; Shen Jian Tao; Suhendro Yusuf Irianto (Prosiding International conference on Information Technology and Business (ICITB), 2020)
Car rental was one of the business entities in the field of four-wheeled vehicle/cars rental services. The information system for borrowing and returning cars in Lampung was considered effective because the data of borrowing and returning cars and the daily transactions were recorded and reported manually - in the written form such as books and paper – so that this system was inefficient in terms of saving time, energy, and materials. The objective of this study was to build the website-based information system for car rental businesses in Lampung. The method used in this study was a structured approach method through the prototype development. The data collecting techniques used in this study was observation and interviews. The analysis and designing tools used in this study were the case diagrams, 0- levelled data flow diagrams, and 1-levelled flow diagrams. The supporting software used in this study was PHP and MySQL database. The sublime was an idea used to expanding the web application using PHP. This tool was facilitated to use to symbol, word, or line using a keyboard shortcut in a quick way. The result of this study was that the information system for borrowing and renting the car for car rental service was expected to facilitate the employees in managing the data of customers, borrowing and returning cars, and reducing errors from the data records and reports.Keywords:Information Systems, Car Rental, Borrowing, Refund.